The Effect of Infant Massage on Weight Gain in Low Birth Weight Infant: A Case Study - Hasti Mahmudah; Rahmah Rahmah; Siti Nurjanah (Stikes Syedza Saintika Padang, 2025)
Infant mortality rate remains a major public health issue in many countries, including Indonesia. One of the contributing factors to the high infant mortality rate is low birth weight, which can lead to various health complications. This study aims to analyze the effect of infant massage on weight gain in infant with low birth weight. A case study design was used, involving an infant diagnosed with low birth weight. The primary data collection methods included observation and weight measurement before and after the infant massage intervention. Data analysis was conducted by comparing weight changes before and after regular massage sessions. The results indicate that infant massage significantly contributes to weight gain in low birth weight infant. This is evidenced by a gradual increase in weight, from 1,265 grams on the first day to 1,420 grams on the seventh day, with an average weight gain of 155 grams per week, with an average daily weight gain of 22.14 grams. Therefore, infant massage can serve as an alternative approach to support the growth of infant born with low birth weight. The implications of this study suggest that infant massage can be incorporated into nursing practices as a strategy to enhance the health of low birth weight infants.